Corporate R&D leaders reflect on their mutual European future. - Sweet, W. (IEEE spectrum)
Amid ominous rumblings in the world economy, suggesting that ?globalization? may be entering stormy waters or worse, Europe is poised to embark on the final and, some say, most perilous phase of creating a truly-common market. If Europe manages to stay the course and inaugurates the single currency, the stage will be set for full integration of commercial, financial, and labor markets. Already the continent's political leaders are looking beyond strictly economic unification to larger concerns: meeting in Amsterdam two years ago, they agreed, for example, to start harmonizing visa and asylum policies, to more closely coordinate international police work under the aegis of Europol, and for the first time to give the European Commission in Brussels some military muscle for peace keeping and humanitarian intervention. How, under these complex circumstances, do corporate research strategists assess the common European future. To obtain some soundings in a variety of settings, IEEE Spectrum conducted interviews with research strategists of Philips Electronics NV, ST Microelectronics, and ABB-three very different kinds of companies. The research strategists see positive trends but also some cause for alarm. The interviews are given in this paper